2022
DOI: 10.1021/acs.jpclett.2c00193
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Role of Electronic Doping for Developing Cocatalyst-Free Semiconducting Photocatalysts

Abstract: Developing cocatalyst-free photocatalysts is highly desired because it could avoid the very slow interfacial electron transfer that makes photocatalytic photon utilization a dilemma. However, even in the optimal case, photocatalysts without the use of cocatalysts deliver comparable performance only for conventional construction. We demonstrate here that electronic doping not only provides catalytically active sites in cocatalyst-free photocatalysts but also plays certain additional roles. These electronic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Recently, we found that semiconductor–cocatalyst (SC) interfacial electron transfer in photocatalytic reactions occurs on a decisecond–second time scale (Figures a,d, , and S2). ,, This value is 6–12 orders of magnitude larger than the widely believed picosecond–microsecond time scale and is comparable to the that of >1 s predicted by Durrant et al , This finding not only reveals that SC interfacial electron transfer is the rate-determining step in photocatalytic reactions but also provides rational elucidation to the very low utilization of incident photons . Interestingly, the time constants for SC interfacial electron transfer occurring in a fixed bed reaction is comparable to that in a slurry suspension (Figures and S2).…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Recently, we found that semiconductor–cocatalyst (SC) interfacial electron transfer in photocatalytic reactions occurs on a decisecond–second time scale (Figures a,d, , and S2). ,, This value is 6–12 orders of magnitude larger than the widely believed picosecond–microsecond time scale and is comparable to the that of >1 s predicted by Durrant et al , This finding not only reveals that SC interfacial electron transfer is the rate-determining step in photocatalytic reactions but also provides rational elucidation to the very low utilization of incident photons . Interestingly, the time constants for SC interfacial electron transfer occurring in a fixed bed reaction is comparable to that in a slurry suspension (Figures and S2).…”
supporting
confidence: 73%
“…For many photocatalytic reactions of integrated HE with organic substance oxidation, the concentration of organic solute can be >1 mol/L and the maximal flux of reactant can be >2 × 10 –6 mol cm –2 s –1 , which is at least 1 order of magnitude larger than the photocatalytic reaction rate in the level of 10 –7 mol cm –2 s –1 under intense irradiation. The time scale for diffusion of reactant(s) can be only 0.1–0.5 s (Figure b), which is mainly smaller than the range from several deciseconds to several seconds for SC interfacial electron transfer (Figures d and ). ,, ,, This suggests that mass transport cannot be an influencing factor in the photocatalytic fixed bed reactions.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…[13][14][15] This measure can modify the electronic states that influence the chemical activity of the semiconductor surface, [16][17][18] and the electronic processes including electron transport in the interior of the semiconductor and interfacial transfer of electrons to the cocatalysts. 19,20 Since the increase in the density of electronic states will undesirably prolong the detrapping time during electron transport and aggravate the charge leakage, 16,[21][22][23][24][25][26][27][28][29] it is desired to facilitate the rate-determining step in the forward reaction without exacerbating the detrimental effect by accurate elementary doping.…”
Section: Introductionmentioning
confidence: 99%